Transformation of Health Promotion in the Digital Era: A Case Study on the Utilization of Wedang Uwuh as a Traditional Herbal Medicine in Yogyakarta - Dewi, Riskha Dora Candra (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
The transformation of health promotion in the digital era presents new opportunities to introduce and enhance public awareness of traditional herbal medicine, including Wedang Uwuh. However, challenges such as competition with modern health products and a lack of public awareness regarding the benefits of herbal remedies remain obstacles in promoting this product. Therefore, this study aims to explore the utilization of digital communication technology in the promotion of Wedang Uwuh in Yogyakarta and analyze its impact on public awareness and acceptance. This research employs a qualitative methodology with a case study approach. Data were collected through a literature review, analyzing scientific articles, reports, and case studies related to digital health promotion, the use of traditional herbal medicine, and communication technology in Indonesia. This approach enables a deeper understanding of the promotional strategies used, the challenges faced, and the opportunities for integrating digital technology with local health traditions. The findings indicate that the use of digital technology, such as social media, websites, and health applications, has contributed to increasing public awareness and acceptance of Wedang Uwuh. However, barriers such as the digital divide and limited technological literacy among small business owners remain significant challenges in optimizing digital promotion. Therefore, collaboration between the government, business actors, and local communities is necessary to overcome these challenges and maximize the potential of digital technology in supporting the promotion of traditional herbal products in Indonesia.